Differential Effect of Electroacupuncture on Inflammatory Adipokines in Two Rat Models of Obesity - Jacqueline J.T. Liaw; Philip V. Peplow (Medical Association of Pharmacopuncture Institute, 2016)
Chronic inflammation is known to be associated with visceral obesity and insulin resistance which are characterized by altered levels of production of pro- and anti-inflammatory adipokines. The dysregulation of the production of inflammatory adipokines and their functions in obese individuals leads to a state of chronic low-grade inflammation and may promote obesity-linked metabolic disorders and cardiovascular diseases such as insulin resistance, metabolic syndrome, and atherosclerosis. Electroacupuncture (EA) was tested to see if there was a difference in its effect on pro- and anti-inflammatory adipokine levels in the blood serum and the white adipose tissue of obese Zucker fatty rats and high-fat diet-induced obese Long Evans rats. In the two rat models of obesity, on Day 12 of treatment, repeated applications of EA were seen to have had a significant differential effect for serum tumor necrosis factor-α, adiponectin, the adiponectin:leptin ratio, and blood glucose. For the adipose tissue, there was a differential effect for adiponectin that was on the borderline of significance. To explore these changes further and how they might affect insulin resistance would require a modification to the research design to use larger group sizes for the two models or to give a greater number of EA treatments.